Neoliberal Ebola Modeling Disease Emergence from Finance to Forest and Farm - Wallace, Robert G.; Wallace, Rodrick (Springer International Publishing : Imprint: Springer, 2016)
This book compiles five papers modeling the effects of neoliberal economics on the emergence of Ebola and its aftermath. The multidisciplinary teams represented here place both Ebola Makona, the Zaire Ebola virus variant that has infected 28,000 in West Africa, and Ebola Reston, which is currently emerging in industrial hog farms in the Philippines and China, within a multi-plank modeling framework. This volume proposes an alternate science of disease and an adjunct program of interventions useful to researchers and public health officials alike. .